Sobre la dinámica de campos vectoriales polinomiales cuasi-homogéneos y sus perturbaciones - Santaella Forero, Rubén Darío (Universidad Michoacana de San Nicolás de Hidalgo. Universidad Nacional Autónoma de México, 2016)
In this work, the nonexistence of limit cycles for classes of p - q-quasihomogeneous polynomial planar systems of weighted degree l is established. Furthermore, we rule out the existence of limits cycles for certain perturbations of such planar systems. We present applications and examples in order to illustrate our results.

In this work, the nonexistence of limit cycles for classes of p - q-quasihomogeneous polynomial planar systems of weighted degree l is established. Furthermore, we rule out the existence of limits cycles for certain perturbations of such planar systems. We present applications and examples in order to illustrate our results.
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Programa Conjunto de Maestría en Matemáticas
Keywords: info:eu-repo/classification/cti/1; IFM-M-2016-0124; Ciclos; Sistemas; Epidemiología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1226